Imperialismo e novo constitucionalismo na América Latina: a questão da terra em Bolívia e Equador - Brum, Márcio Morais (2017)
Faced with the concrete reality of the new imperialism's advance through the spoliation of Latin America through the processes of land alienation and intensification of export agribusiness and, on the other hand, of the new constitutions of countries like Ecuador and Bolívia, which institute the principle of buen vivir and the rights of Pachamama, the paper intends to analyze the relationship between imperialism via espoliation and new Latin American constitutionalism, with a view to answering: what kind of relationship is there between the two concepts / phenomena? Are they antithetical to each other? Can it be said that the new Latin American constitutionalism consists of an anti-imperialist legislative movement and legal set? With this, the investigation seeks to arrive at a synthesis on the conceptual and concrete relationship between imperialism via plunder and new Latin American constitutionalism. In order to reach the established objectives, the author adopts as a research technique the bibliographic review. It observes, from the outset, that the relationship between imperialism via espoliation and the new Latin American constitutionalism is at the same time a relation between concepts and a relation established in concrete reality. Against this, the investigation proceeds from data on the advance of the new imperialism in Latin America (especially on the foreignization of land and the advancement of agribusiness) that are confronted with the constitutional normativity of Bolívia and Ecuador in order to verify what has been the concrete synthesis between Imperialism via espoliation and new constitutionalism. The development of the work shows that the new Latin American constitutionalism, partially the product of anti-colonial popular aspirations, brings within it two fundamental concepts: Pachamama e buen vivir. The former, by not accepting the possibility of marking the land and the beings that inhabit it, is incompatible with the capitalist mode of production and essentially contrary to any imperialist longing for the spoliation of natural wealth. The second, because it is also incompatible with the marking of nature, contradicts the capitalist / imperialist logic that causes imbalances and disharmonies. However, Pachamama's rights and the principle of buen vivir alone are incapable of producing the desired transformations of reality, since they do not themselves institute the mechanisms necessary for their realization. This requires the existence of constitutional precepts that block the commodification and spoliation of nature. Contradictory, however, the Constitutions of Ecuador and Bolívia assure the maintenance of the capitalist mode of production, reason why it is not possible to be affirmed that the new constitutionalism, in the current configuration, consists in a normative standard antitético to the imperialism. In terms of concrete social relations, the new constitutionalism presents the contradictions typical of a class society, based on the capitalist mode of production and linked to the world economy in a situation of dependency, which makes it incapable of completely blocking harmful spoliation imperialist practices To the full realization of the good life and the realization of the rights of Pachamama.